ChemInform Abstract: Triflic Acid Catalyzed Intermolecular α‐Amination of Pterolactams to Give 5‐Arylaminopyrrolidinones via N‐Acyliminium Species. Issue 33 (July 2016) - Dumitriu, Gina‐Mirabela; Bicu, Elena; Eryuruk, Ulku; Belei, Dalila; Rigo, Benoit; Daich, Adam; Ghinet, Alina
Abstract: Compounds (IIId), (IIIe), (IIIf), (VIII), and (XII) show inhibitory activity against human farnesyltransferase.